Determinants of Environmental Information Disclosure in Blue Category of PROPER Assessment - Ari Purwanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The need for environmental information disclosure on the activities of companies classified as "reactive" or companies with the PROPER assessment category in blue at this time, prompted this study to try to investigate the factors that could influence it. The level of effectiveness of loans in an effort to increase the rate of return on asset performance is the point of view in this study. This study aims to test the hypothesis of a measure of environmental information from the Indonesian Environmental Reporting Index. This study used 18 companies as samples with the PROPER-blue category. The results of empirical testing prove that the level of loan effectiveness has a negative and significant effect on the extent of environmental information disclosure and the rate of return on asset performance has a positive and significant effect on the extent of environmental information disclosure. The implications of the results of this study are expected to be a reference for better disclosure of environmental management.